1997
DOI: 10.1001/archsurg.1997.01430250015002
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Thoracic Duct Lymph in Multiple Organ Dysfunction Syndrome

Abstract: Our results provide evidence of the participation of the gut-associated lymphatic tissue in the pathogenesis of the multiple organ dysfunction syndrome, suggesting that T-cell activation and cytokine production occur at the gut level. Future studies are needed to confirm and extend our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…(33-34) In case reports of patients with MOF, thoracic duct sampling has confirmed increased lymph: plasma levels of IL-1 (3, IL-6 and IL-10. (35-37)…”
Section: Dysfunctional Immune Response Is Central In the Pathogenesismentioning
confidence: 99%
“…(33-34) In case reports of patients with MOF, thoracic duct sampling has confirmed increased lymph: plasma levels of IL-1 (3, IL-6 and IL-10. (35-37)…”
Section: Dysfunctional Immune Response Is Central In the Pathogenesismentioning
confidence: 99%
“…Other studies have demonstrated bacterial translocation to mesenteric lymph nodes [31,32]. Furthermore, mesenteric lymph has subsequently been demonstrated to be a conduit for interleukin-1, interleukin-6, and tumor necrosis factor, but until recently the concept that the mesenteric lymph is the mechanistic link to MOF had not been explored [33][34][35]. In a very provocative report Deitch has recently reported the profound observation that mesenteric lymph diversion eliminates lung injury caused by hemorrhagic shock [7].…”
Section: Figmentioning
confidence: 99%
“…The findings of this present study along with those of Deitch et al make the search for the etiologic agents in the mesenteric lymph very attractive. Postshock mesenteric lymph contains proinflammatory mediators such as interleukin-6, interleukin-1, and TNF [33][34][35]. The fact that mesenteric lymph taken within minutes following shock primes PMNs would indicate that, if cytokines are the etiologic agent, they would need to be preformed and rapidly secreted.…”
Section: Figmentioning
confidence: 99%
“…3 Subsequent clinical studies have supported this finding. 21,22 After the bacterial translocation mechanism failed to satisfy Koch's postulates, the lymphatic system became the target of investigation as the primary conduit for delivering inflammatory factors from the ischemic gut into the circulation.…”
Section: Discussionmentioning
confidence: 99%